1970
DOI: 10.4314/ahs.v19i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Renal risk profiling in newly diagnosed hypertensives in an urban population in Nigeria

Abstract: Introduction: Hypertension is a cause and consequence of chronic kidney disease globally. The other factors that work in concert with hypertension to cause CKD are yet to be clearly elucidated. Studies have identified proteinuria, dyslipidemia, obesity, smoking and family history of CKD as renal risk factors. Due to the high morbidity and mortality associated with occurrence of CKD including the enormous financial burden involved in its management, the knowledge of prevention and understanding of the risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
(1 reference statement)
3
4
1
Order By: Relevance
“…Even though our study did not assess intensity of use, current alcohol use was associated with higher odds of hypertension in the adjusted regression model. Our findings agree with previous studies that found alcohol intake and/or binge drinking was associated with hypertension among Nigerians [ 50 , 62 , 63 ]. The high prevalence of alcohol use in this study population, which is similar to what obtains in the general population [ 64 ] suggests that alcohol use is another modifiable risk factor that can be targeted for both primary and secondary prevention of hypertension in Nigeria.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Even though our study did not assess intensity of use, current alcohol use was associated with higher odds of hypertension in the adjusted regression model. Our findings agree with previous studies that found alcohol intake and/or binge drinking was associated with hypertension among Nigerians [ 50 , 62 , 63 ]. The high prevalence of alcohol use in this study population, which is similar to what obtains in the general population [ 64 ] suggests that alcohol use is another modifiable risk factor that can be targeted for both primary and secondary prevention of hypertension in Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…Studies reviewing adult medical inpatient admissions consistently place hypertension and its complications among the top five causes of hospital admission and mortality [45][46][47][48]. Additionally, there is evidence that many hypertensive patients already have end organ damage at presentation for initial care in Nigeria [49,50]. These findings suggest that many Nigerians with hypertension may be receiving their diagnosis late, and suffering avoidable morbidity and mortality as a result.…”
Section: Plos Onementioning
confidence: 99%
“…In a Nigerian community study including around 1,500 participants, Olanrewaju et al 54 found that obesity defined using the waist-to-hip ratio, not waist circumference or BMI, was associated with CKD (odds ratio, 1.5; 95% confidence interval, 1.10-2.05) ( Table 1 ). 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 In a cross-sectional study among teachers in South Africa, waist circumference was significantly associated with CKD, and in Senegal, a higher BMI was associated with CKD. 55 , 56 When participants with CKD were compared with those without CKD in a cross-sectional study from the Cape Town Vascular and Metabolic Health study, a significantly higher BMI (30.4 vs 28.2 kg/m 2 ), waist circumference (99 vs 90.8 cm), and visceral adipose tissue (228.4 vs 174.9 cm 2 ) were reported, but there was no significant difference in subcutaneous adipose tissue.…”
Section: Obesity and Ckd In Sub-saharan Africa: Choice Between Waist ...mentioning
confidence: 99%
“…10 Guagnano et al and Ferroni et al found a positive linear association between platelet activation and presence of microalbuminuria in their study this is attributed to high blood pressure and the endothelial dysfunction, which causes activation of platelets this will manifest as increased MPV and PDW. 15 Endothelial dysfunction in hypertensives with microalbuminuria are reflected by decreased levels of NO and increased plasma levels of ICAM-1 in the patients with microalbuminuria. 15 Cause of microalbuminuria can be traced to structural and functional transformational process in the glomeruli (endothelium, glomerular basal membrane, podocytes) that are associated with increased permeability.…”
Section: Hypertensive Mediated Kidney Disease and Platelet Indicesmentioning
confidence: 99%
“…15 Endothelial dysfunction in hypertensives with microalbuminuria are reflected by decreased levels of NO and increased plasma levels of ICAM-1 in the patients with microalbuminuria. 15 Cause of microalbuminuria can be traced to structural and functional transformational process in the glomeruli (endothelium, glomerular basal membrane, podocytes) that are associated with increased permeability. Interestingly, this permeability disorder is not limited to the renal vessels but can be observed in the entire vascular system.…”
Section: Hypertensive Mediated Kidney Disease and Platelet Indicesmentioning
confidence: 99%